Financing the Development of Old Waqf Properties [electronic resource] : Classical Principles and Innovative Practices around the World - Mohsin, Magda Ismail Abdel; Dafterdar, Hisham; Cizakca, Murat; Alhabshi, Syed Othman; Razak, Shaikh Hamzah Abdul; Sadr, Seyed Kazem; Anwar, Thamina; Obaidullah, Mohammed; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2016)
This book presents successful case studies in Muslim and Muslim minority countries that have revolutionized the redevelopment of idle waqf properties into productive land trusts. The revival of this institution over the last two decades shows the growing optimism in galvanizing the socioeconomic role of waqf by adopting its flexible shariah measures. Innovative ways of financing redevelopment allow Muslims to extend these roles to include new beneficiaries. New uses for these properties include providing services to the community, opening jobs for the majority of people, funding small entrepreneurs, educating the masses, providing health care, and sheltering the poor and needy. Countries under study include Sudan, Turkey, Malaysia, Indonesia, Singapore, New Zealand, Kuwait, Oman, Qatar, and Iran. Additionally, the book examines the International Development Bank's role in financing the development old waqf properties in different countries.
1 Legal Framework of the Institution of Waqf -- 2 Development and Administration of the Instition of Waqf, Past and Present -- 3 The Role of Waqf in Modern Economic Development -- 4 Current Development of Waqf Properties in Selected Countries and their Socioeconomic Roles -- 5 Waqf Development: The Islamic Development Bank Experience -- 6 Modus Operendi and the Structures of both Classical and Innovative Modes of Finance -- 7 Conclusion.
Keywords: Finance; Banks and banking; Finance; Banking